Thermal degradation behavior and flame retardant properties of PET/DiDOPO conjugated flame retardant composites* - Xiang, Yushu; Gao, Yun; Xu, Guomin; He, Min; Qin, Shuhao; Yu, Jie (Frontiers in Chemistry, 2022)
PET/DIDOPO conjugated flame retardant composites were prepared by melt blending of styrene bridged DOPO (DIDOPO) into polyethylene terephthalate (PET). The flame retardancy, rheological behavior, and thermal degradation behavior of the composite were characterized by vertical combustion test (UL-94), limit oxygen index test (LOI), rotational rheometer, and thermogravimetry (TG). The results showed that the flame retardant composite with V-0 grade was obtained when the amount of DIDOPO is 12.5wt%, and the corresponding LOI value was 56.87% higher than that of PET. The thermogravimetry-fourier infrared spectroscopy (TG-FTIR) test results showed that DIDOPO could promote the degradation of PET/DIDOPO materials, and release phosphorus-containing free radicals to quench the flame, therefore slowing down the combustion process, and mainly playing the key flame retardant role in gas-phase.